2018
DOI: 10.1111/1751-7915.13315
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ microbially induced Ca2+‐alginate polymeric sealant for seepage control in porous materials

Abstract: Summary This paper presents a novel approach of using in‐situ microbially induced Ca 2+ ‐alginate polymeric sealant for seepage control in porous materials. This process comprises two steps: (i) generation of insoluble calcium carbonate inside the pores of porous materials (such as sand) through a microbially induced carbonate precipitation ( MICP ) process in‐situ and (ii) injection of sodium alginate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…However, the use of bacteria for experimental purposes in actual in-situ conditions can be sensitive. Alternatively, enzymes can be used instead, and enzyme or polymer-based methods have also been developed in recent years (Khatami and O'Kelly, 2013;Cheng et al 2019;He et al 2020).…”
Section: Pathogen-soil Interactionsmentioning
confidence: 99%
“…However, the use of bacteria for experimental purposes in actual in-situ conditions can be sensitive. Alternatively, enzymes can be used instead, and enzyme or polymer-based methods have also been developed in recent years (Khatami and O'Kelly, 2013;Cheng et al 2019;He et al 2020).…”
Section: Pathogen-soil Interactionsmentioning
confidence: 99%
“…e test results showed that the construction process can effectively reduce the permeability coefficient of the sand surface and thus meet the engineering requirements. Cheng et al [121] applied CaCO 3 precipitation techniques combined with the reaction of sodium alginate with Ca 2+ ions to form a gel-like calcium alginate for sand seepage control treatment. e test results showed that the permeability of the treated sand decreased from 5.0 × 10 −4 m/s to 2.2 × 10 −9 m/s and that the seepage control efficiency increased by one to two orders of magnitude compared to that treated with pure MICP technology.…”
Section: Foundation Seepage Controlmentioning
confidence: 99%
“…1, stiffness [115,118,[123][124][125][126][127][128][129][130][131][132], and thermal conductivity [133,134], etc. Some studies also proposed to further enhance the strength of bio-cemented soil by adding other materials, such as lime [42], fiber [54,125,[135][136][137][138][139][140][141][142][143], hydrogelassisted [144], the hydrophilic polymer [145,146], and alginate [147]. MICP based soil improvement involves a highly complex biological, physical and chemical process, which is mainly affected by the following four aspect factors: 1) soil properties, 2) urease producing bacteria (UPB) characteristics, 3) cementation solution (CS) parameters, and 4) treatment process.…”
Section: Strength Enhancement Of Soilmentioning
confidence: 99%
“…Cementation solution (CS) is usually a mixture of calcium and urea. Some other substances may also be added to the CS in some studies, such as nutrient broth, NH 4 Cl and NaHCO 3 [14,38,123,146,152,155,157,199,206,[212][213][214][215][216][217], yeast extract [31,184], Tris base [31], sodium malate [38], sodium acetate [48,184], and polyvinyl alcohol [146]. Chen et al [218] also proposed to use urine as the urea source for MICP treatment.…”
Section: Cementation Solution Parametersmentioning
confidence: 99%